Enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR) analysis among raw vegetables isolates of Campylobacter Jejuni / Tuan Suraya Tuan Soh - Tuan Soh, Tuan Suraya (2010)
A total of 20 (n=20) raw vegetable isolates of Campylobacter jejuni were examined for the presence of virulence genes and genetic diversity using enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) analysis. All C. jejuni isolates were obtained from the laboratory of Food Science and Biotechnology, University Putra Malaysia, Serdang, Selangor. When specific PCR amplification were determined, all raw vegetables isolates of Campylobacter jejuni contained cadF and ceuE genes. Whereas, 12 (12/20) isolates were positive cdtB and 6 (6/20) were positive cdtC. None of the C. jejuni isolates was cdtA positive. Using ERIC-PCR analysis, all 20 isolates of C. jejuni were subtyped and produced 18 ERIC-PCR profiles namely E1 to E18. Dendogram performed from cluster analysis showed the 20 isolates were group into 2 major clusters (cluster I and II) which may suggest the high level of local geographical genetic variation. From this study, the detection of virulence gene among Campylobacter jejuni strains isolated from raw vegetables is an evidence that raised concern on treatment of campylobacteriosis.